(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
In the current study determination of the natural and artificial activity level on samples sediment the Euphrates River on Babylon governorate using -ray spectrometry technique with NaI(Tl) detector. Where 50 samples of sediment Euphrates river. The results revealed that the average values in( Bq/kg) for Uranium , Thorium Potassium And , and samples sediment were ( 21.815, 5.326, 273.377, 0.879) respectively. The hazard indexes were also calculated, where the radium average equivalent activity Raeq was 56.084 , And Hazard index for -ray ( ) was 0.420 , The average absorbed does in Air (AD) was 27.347, The results of the present study have shown that the rates of Specific activity and radiological hazard effects Rate for Gamma ray in samples sediment the Euphrates River on Babylon governorate were all lower than the value of the global limit.